The Influence of Children's Gadget Use Intensity on Their Social Skills - Nurhafani, Meilenia; Kurniawati, Yuli; Pranoto, Sugiyo; Nuzulia, Siti (JURNAL PENDIDIKAN USIA DINI, 2023)
Social skills play an important role in preventing negative behavior and can be developed every day. It depends on temperament, social cognitive abilities, and interactions. This research aims to determine the effect of the intensity of gadget use by young children on their social skills. Apart from that, the aim is to determine the influence of gadget use by young children on gadget use which is mediated by parents' social skills. This research uses a quantitative method design through observation techniques and questionnaires. The research results showed a significant influence on the intensity of gadget use by children in the Patikraja area on social skills (P = 0.742; P > 0.05). The intensity of gadget use of PAUD students in Patikraja which is mediated by parents' gadget use on social skills has a significant effect (P=0.001; P<0.05) with B values of -0.61 and -5.345. The increasing intensity of gadget use by children in Patikraja, mediated by the intensity of parents' gadget use, causes a decline in social skills of 7.6%. This shows a significant influence between the intensity of gadget use by children and their social skills which is mediated by the intensity of parents' gadget use. Keywords: intensity, gadgets, social skills References: Al Sagr, N. A., & Al Sagr, A. N. (2020). The effect of electronics on the growth and development of young children : A Narrative Review. Journal of Health Informatics in Developing Countries, 14(1), 1–13. https://jhidc.org/index.php/jhidc/article/view/250 Alexander L., K., & Hamzah, H. (2018). Exploratory analysis of pilot data: Trends of gadget use and psychosocial adjustment in pre-schoolers. Southeast Asia Early Childhood Journal, 7(Mcmc), 14–23. https://doi.org/10.37134/saecj.vol7.2.2018 Ardoin, N. M., & Bowers, A. W. (2020). Early childhood environmental education: A systematic review of the research literature. Educational Research Review, 31, 100353. https://doi.org/10.1016/j.edurev.2020.100353 Arikunto, S. (2016). Prosedur Penelitian Suatu Pendekatan Praktik. PT Rineka Cipta. Bräuninger, I., & Röösli, P. (2023). Promoting social-emotional skills and reducing behavioural problems in children through group psychomotor therapy: A randomized controlled trial. Arts in Psychotherapy, 85(January). https://doi.org/10.1016/j.aip.2023.102051 Bruno, C., & Donaldson, C. (2018). Combining the best aspects of humanity with the best of technology. Childhood Education, 94(6), 25–32. https://doi.org/10.1080/00094056.2018.1540194 Cáceres, I., Moreno, C., Román, M., & Palacios, J. (2021). The social competence of internationally-adopted and institutionalized children throughout childhood: a comparative and longitudinal study. Early Childhood Research Quarterly, 57, 260–270. https://doi.org/10.1016/j.ecresq.2021.07.002 Cahyani, A., Atmaja, K., & Widodo. (2021). The role of parents in monitoring the negative impacts of gadget usage for early childhood during Covid-19 pandemic era. Advances in Social Science, Education and Humanities Research, 618, 1105–1116. https://doi.org/10.2991/assehr.k.211223.194 Calorina, L., Pawito, & Prasetya, H. (2020). The effect of gadget use on child development: A path analysis evidence from Melawi, West Kalimantan. Journal of Maternal and Child Health, 5(1), 110–119. https://doi.org/10.26911/thejmch.2020.05.01.12 Carson, V., Lee, E.-Y., Hesketh, K. D., Hunter, S., Kuzik, N., Predy, M., Rhodes, R. E., Rinaldi, C. M., Spence, J. C., & Hinkley, T. (2019). Physical activity and sedentary behavior across three time-points and associations with social skills in early childhood 11 Medical and Health Sciences 1117 Public Health and Health Services. BMC Public Health, 19(1), 1–8. https://doi.org/10.1186/s12889-018-6381-x Choi, Y. J., & Asilkalkan, A. (2019). R packages for item response theory analysis: Descriptions and features. Measurement: Interdisciplinary Research and Perspectives, 17(3), 168–175. https://doi.org/10.1080/15366367.2019.1586404 Dalmacio, J. M. M., Robosa, J. D., Espinosa, J. F., Cabria, C. M. O., Alvez, J., Maranan, L. A. F., Aglamma, J. A. E., Artiola, A. S., & Templonuevo, W. (2023). Exploring the implication of gadget use towards school and behavior of middle childhood: A mother’s perspectives. Psychology and Education, 7, 741–750. https://doi.org/10.5281/zenodo.7750846 Ekyana, L., Fauziddin, M., & Arifiyanti, N. (2021). Parent’s perception: Early childhood social behaviour during physical distancing in the covid-19 pandemic. JPUD - Jurnal Pendidikan Usia Dini, 15(2), 258–280. https://doi.org/10.21009/jpud.152.04 Frogner, L., Hellfeldt, K., Ångström, A., Källström, Å., Fanti, K. A., & Andershed, H. (2022). Stability and Change in Early Social Skills Development in Relation to Early School Performance : A Longitudinal Study of A Swedish Cohort Stability and Change in Early Social Skills Development in Relation. Early Education and Development, 33(1), 17–37. https://doi.org/10.1080/10409289.2020.1857989 Hambleton, R. K., & Swaminathan, H. (2013). Item response theory: Principles and applications. Springer Science & Business Media. Hidayati, N., & Zaman, B. (2021). Is it necessary to ban gadget in early childhood? Advances in Social Science, Education and Humanities Research, 538(Icece 2020), 270–273. https://doi.org/10.2991/assehr.k.210322.057 Hori, K., Fukuhara, H., & Yamada, T. (2022). Item response theory and its applications in educational measurement part I: Item response theory and its implementation in R. Wiley Interdisciplinary Reviews: Computational Statistics, 14(2), 1–22. https://doi.org/10.1002/wics.1531 Howard, M. C., & Gutworth, M. B. (2020). A meta-analysis of virtual reality training programs for social skill development. Computers and Education, 144(June 2019), 103707. https://doi.org/10.1016/j.compedu.2019.103707 Hurlock, E. B. (2004). Perkembangan Anak (A. Dharma (ed.); 6th ed.). Erlangga. Hussein, M. H. (2011). Evaluation of an Arabic version of children’s Self-report Social skills scale (CS4) based on Item Response Theory. Al-Majla Al-Masriah Ledrasat Al-Nafsial-Nafsia, 21(70), 537–562. Inomjonovna, R. ., & Erkinovna, E. . (2023). Social pedagogical factors for preventing aggresive situations children in preschool educatiom. Journal of New Century Innovations, 12(2), 29–34. https://doi.org/10.30687/elle/2280-6792/2023/02 Inomjonovna, R. ., & Maxmudjon qizi, S. . (2022). Factor for the development of imaging skills of preschool children. The Theory of Recent Scientific Research in The Field of Pedagogy, 74–79. Madhava, R., Mk, R., & Bhuvaneshwari, D. (2021). Impact of intervention in gadget usage among children. Journal of Women’s Health & Safety Research JWHSR, 5(1), 198–201. www.scitcentral.com Maleki, M., Chehrzad, M. M., Leyli, E. K., Mardani, A., & Vaismoradi, M. (2019). Social skills in preschool children from teachers’ perspectives. Children, 6(5), 1–12. https://doi.org/10.3390/children6050064 Maleki, M., Mardani, A., Chehrzad, M. M., Dianatinasab, M., & Vaismoradi, M. (2019). Social skills in children at home and in preschool. Behavioral Sciences, 9(7), 1–15. https://doi.org/10.3390/bs9070074 Marif, A. (2021). The impact of using smartphone on early childhood. European Journal of Education Studies, 8(4), 342–351. https://doi.org/10.46827/ejes.v8i4.3701 Martikainen, S., Kalland, M., Linnavalli, T., Kostilainen, K., Aittokoski, M., Reunamo, J., Vasileiou, Z., & Tervaniemi, M. (2023). Supporting social-emotional development in early childhood education and care – a randomized parallel group trial evaluating the impact of two different interventions. Scandinavian Journal of Educational Research, 1–19. https://doi.org/10.1080/00313831.2023.2204119 Mita Widiastiti, N. L. G., & Sastra Agustika, G. N. (2020). Intensitas Penggunaan Gadget Oleh Anak Usia Dini Ditinjau Dari Pola Asuh Orang Tua. Jurnal Pendidikan Anak Usia Dini, 8(2), 112–120. Neitola, M. (2018). Parents as teachers and Guides of their children’s social skills. Journal of Early Childhood Education Research, 7(2), 392–414. http://jecer.org Novianti, R., & Garzia, M. (2020). Penggunaan Gadget pada Anak; Tantangan Baru Orang Tua Milenial. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(2), 1000. https://doi.org/10.31004/obsesi.v4i2.490 Nuhla, A., Dewanti Handayani, S. S., Formen, A., & Sugiyo Pranoto, Y. K. (2018). Exploring parent’s experience in guiding their children while using gadget at home. Advances in Social Science, Education and Humanities Research, 249, 22–26. https://doi.org/10.2991/secret-18.2018.4 Pardede, E. N., Supena, A., & Fahrurrozi, F. (2018). Hubungan Kelekatan Orangtua Dan Regulasi Diri Dengan Kemampuan Sosial Anak. JPUD - Jurnal Pendidikan Usia Dini, 12(1), 37–50. https://doi.org/10.21009//jpud.121.04 Pratama, M. O., Harinitha, D., Indriani, S., Denov, B., & Mahayana, D. (2020). Influence Factors of Social Media and Gadget Addiction of Adolescent in Indonesia. Jurnal Sistem Informasi, 16(1), 16–24. https://doi.org/10.21609/jsi.v16i1.918 Qutoshi, S. B., Ali, S., & Khan, S. (2021). Use of technological gadget and its effects on children at Agah Walidain Program and beyond during Covid-19 pandemic lockdown. International Review of Social Sciences, 9(2), 22–32. Raine, A., Ang, R. P., Choy, O., Hibbeln, J. R., Ho, R. M. H., Lim, C. G., Lim-Ashworth, N. S. J., Ling, S., Liu, J. C. J., Ooi, Y. P., Tan, Y. R., & Fung, D. S. S. (2019). Omega-3 and social skills interventions for reactive aggression and childhood externalizing behavior problems: A randomized, stratified, double-blind, placebo-controlled, factorial trial. Psychological Medicine, 49(2), 335–344. https://doi.org/10.1017/S0033291718000983 Rizki, M. T., Kustiono, K., & Utanto, Y. (2021). Parent Assistance in The Use of Gadgets for Early Childhood Learning Process. Innovative Journal of Curriculum and Educational Technology, 10(1), 132–139. Sahriana, N., & Sugiyo Pranoto, Y. K. (2018). Perception of preschoolers (3-7 years) on usage of YouTube in Semarang. Advances in Social Science, Education and Humanities Research, 249, 27–33. https://doi.org/10.2991/secret-18.2018.5 Sheridan, S. M., Knoche, L. L., Boise, C., Witte, A., Koziol, N., Prokasky, A., Schumacher, R., & Kerby, H. (2022). Relationships as malleable factors for children’s social-behavioral skills from preschool to grade 1: A longitudinal analysis. Early Education and Development, 33(6), 958–978. https://doi.org/10.1080/10409289.2021.1936374 Sihura, F. (2018). The role of parents “Generation of Z” to the early children in the using of gadget. Advances in Social Science, Education and Humanities Research, 249, 55–59. https://doi.org/10.2991/secret-18.2018.9 Srinahyanti, S., Wau, Y., Manurung, I., & Arjani, N. (2018). Influence of gadget: A positive and negative impact of smartphone usage for early child. Annual Conference of Engineering and Implementation on Vocational Education. https://doi.org/10.4108/eai.3-11-2018.2285692 Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. PT Alfabeta. Sugiyono. (2017). Metode Penelitian Dan Pengembangan. Alfabeta. Sujianti. (2018). The Relationship Between Frequency of Using Gadget and the Social Development of Pre-School Children in Islam Al Irsyad 01 Kindergrten. Journal of Midwifery, 8(1), 54. Unlu, C., & Ceviker, A. (2022). Examination of the Social Skills Levels of Students Participating in Recreative Activities. International Journal on Social and Education Sciences, 4(4), 529–540. https://doi.org/10.46328/ijonses.470 Walker, M. A., & Rinaldi, C. (2020). Children’s Social and Emotional Functioning and Academic Success in Preschool: the Role of Internalizing Problems and Adaptive Skills. Contemporary School Psychology, 24(1), 25–33. https://doi.org/10.1007/s40688-019-00232-5